Social Capital for Community Resilience in Responding to the 2018 Earthquake in the Cupek Community, Lombok - Lestari, Ilyana Agri; Anugrahini, Triyanti (ARISTO, 2023)
Indonesia frequently experiences earthquakes as it is located at the convergence of three highly active tectonic plates, making it prone to natural disasters. Lombok, an island in Indonesia, experienced a series of devastating earthquakes in 2018, resulting in heavy casualties, severe damage and economic repercussions. This research focused on the Cupek community in Sigar Penjalin Village, North Lombok Regency, who demonstrated their resilience and survival capabilities in the aftermath of the earthquakes. Despite limited external assistance during the initial hours following the earthquake, the community swiftly activated their resilience capacities, relying on their social capital and collective actions for support and recovery. This research aims to examine the most significant resilience capacities implemented by the community and explain the process of activating them. This research used the concept of social capital to analyze how the community mobilized their resources and abilities, which ultimately ensured their survival during the initial emergency response. The theoretical framework, data collection and methods of analysis were elaborated and followed by the presentation of specific findings for Cupek. The implications of the research as well as its practical applications for emergency responders and planners were also discussed. The main objective of this research is to enhance the understanding of resilience in small communities, particularly emphasizing the importance of social capital in the context of disasters.Â